Cast extrusion of low gas permeability bioplastic sheets in PLA/PBS and PLA/PHB binary blends. Issue 3 (11th February 2020) - Aversa, C.; Barletta, M.; Puopolo, M.; Vesco, S.
ABSTRACT: Binary blends based on polylactic acid (PLA) and other biodegradable polyesters from renewable sources (namely, polybutylene succinate (PBS) and poly-3-hydroxybutyrate (PHB)) were prepared by reactive compounding extrusion. The achieved polymeric compounds were reprocessed by cast extrusion to manufacture the corresponding bioplastic sheets. Three different binary blends, one of which also including tocopherol, an oxygen scavenger, were investigated to ensure high-barrier of the bioplastic sheets to oxygen permeation. Physical, mechanical and chemical properties of the bioplastic sheets were, therefore, comparatively evaluated by differential scanning calorimetry, infrared spectroscopy, tensile tests and gas permeability. The experimental results showed a remarkable improvement in the oxygen barrier properties, especially on sheets manufactured in the PLA/PHB binary blend, without negatively affecting their thermo-mechanical response. Based on experimental evidences, the PLA/PHB binary blend is found to be extremely promising for the development of bio-based and biodegradable polymeric materials with low oxygen permeation, that is, for the development of suitable alternatives to conventional and highly pollutant oil-based plastics.